Methylmalonic aciduria as a biochemical marker for mitochondrial DNA depletion syndrome in patients with developmental delay and movement disorders: a case series - Almudhry, Montaha; Saini, Arushi Gahlot; Al-Omari, Mohammed A.; Sharma, Yashu; Nouri, Maryam Nabavi; Rupar, C. Anthony; Prasad, Chitra; Yu, Andrea C.; Attri, Savita Verma; Prasad, Asuri Narayan (Frontiers in Neurology, 2023)
Background Mitochondrial DNA (mtDNA) depletion syndromes (MDDS) are genetically and clinically variable disorders resulting from a reduction in mtDNA content in the cells, tissues, and organ systems, leading to symptoms related to energy deficits. Deficiency of the mitochondrial succinyl-CoA ligase/synthetase enzyme secondary to pathogenic variations in the SUCLG1 and SUCLA2 genes is a subtype of MDDS that presents with neurological manifestations and a specific biochemical profile. Methods This cross-sectional series describes five patients with MDDS secondary to pathogenic variations in the SUCLG1 and SUCLA2 genes from two tertiary care centers in Canada and India. Clinical data concerning the course, investigations, and outcome were gathered through chart reviews. Results All subjects presented in early infancy with neurological manifestations, including movement disorder, psychomotor regression, developmental delay, hearing loss, behavioral issues, or a combination thereof. Elevated methylmalonic acid metabolites, an abnormal acylcarnitine profile, and lactic acidemia were noted in the biochemical profile of each patient (n = 5/5, 100%). Molecular genetic testing disclosed the presence of pathogenic homozygous mutations in four subjects and compound heterozygosity in one subject. Conclusion MDDS associated with SUCLG1 and SUCLA2 genes can be detected biochemically by the presence of methylmalonic aciduria besides the elevation of lactate, C3, C4DC, and C5-OH acylcarnitine. Conducting metabolic workups including MMA and acylcarnitine profiles in patients with heterogeneity of clinical symptoms associated with the presence of this biochemical marker may potentially reduce the time to diagnosis and management.